Complex hydrogen bonding and thermal behaviour over a wide temperature range of kainite KMg(SO4)Cl⋅2.75H2O. (February 2022) - Borisov, Artem S.; Siidra, Oleg I.; Ugolkov, Valery L.; Kuznetsov, Alexey N.; Firsova, Vera A.; Charkin, Dmitri O.; Platonova, Natalia V.; Pekov, Igor V.
Abstract: Kainite, KMg(SO4 )Cl⋅2.75H2 O, is one of the most common hydrated sulfate minerals, and it plays an important role as a source of potassium. However, its properties and structure have, to date, been insufficiently studied. In our present work, kainite was investigated using multiple techniques, including single-crystal and powder X-ray diffraction, thermogravimetry, differential scanning calorimetry (DSC), and infrared spectroscopy (IR). The mineral is monoclinic, C 2/ m, a = 19.6742(2), b = 16.18240(10), c = 9.49140(10) Å, β = 94.8840(10)°, V = 3010.86(5) Å 3 and Z = 16. The structure was refined to R 1 = 0.0230 for 3080 unique observed reflections with | F o | ≥ 4σ F . The complex hydrogen bonding system for kainite is described for the first time. The structure of kainite contains seven symmetrically independent sites occupied by water molecules, six of which are strongly bonded to Mg 2+ cations while the seventh resides in the framework cavities. The acceptors of the hydrogen bonds are either chloride anions, neighbouring water molecules or oxygens atoms of sulfate groups. A bifurcated hydrogen bond was described for one of the water molecules. Based on the analysis of the crystal structure, we have confirmed and propose the correct formula for kainite as KMg(SO4 )Cl⋅2.75H2 O. The thermal studies of kainite in the temperature range of –150°C to +600°C indicate its stability to 190°C. The decomposition products are K2 Mg2 (SO4 )3, KCl and K2 SO4 . The thermal expansion was calculated, which for kainite has a character typical for monoclinic crystals and similar to the compressibility tensor described earlier.